HUKUM DAN KEADILAN - Hutabarat, Dany Try Hutama; Mustafa, Suci Irbatia; Ranti, Delfi; Samosir, Riski Hamsyah; Juwita, Salsadila; Lingga, Robi; Marpaung, Maysaroh; Nasution, Ika Bina Prasanti; Riski, Fajar; Syah, Perdana; Azzahro, Wan; Mariza, Rahma (Nusantara Hasana Journal, 2022)
Law is rule in the from of norms and sactions made with the intention to regulate all human behavior, maintain public order, for justice and to prevent chaos in all levels of society. Law is very important for humans, esepecially for regulating human life it self in an ordely and peaceful manner as well as directed and ordely in accordance with the function of law. Justice and law are closely related because the creation of law must be able to provide the value of justice in the law. In enforcing a law, the law must also uphold justice according the needs and portions of each. The real ideals of law are legal certainty, legal benefits, and legal justice. Justice is actually an element of the law created to regulate all human behavior anf human thought patterns.